Notes on the genus Lagocheirus Dejean: records and descriptions (Coleoptera: Cerambycidae: Lamiinae: Acanthocinini) - Toledo, Víctor H.; Hovore, Frank T. (Zootaxa, 2005)
Lagocheirus jamaicensis is described as new from Jamaica. Lagocheirus araneiformis flavolineatus Aurivillius is proposed as a new status. Taxonomic notes and characterizations are provided for L. foveolatus and L. giesberti; species discussed are illustrated in color.